Identification of key gene networks controlling polysaccharide accumulation in different tissues of Polygonatum cyrtonema Hua by integrating metabolic phenotypes and gene expression profiles - Chen, Longsheng; Xu, Shuwen; Liu, Yujun; Zu, Yanhong; Zhang, Fuyuan; Du, Liji; Chen, Jun; Li, Lei; Wang, Kai; Wang, Yating; Chen, Shijin; Chen, Ziping; et al. (Frontiers in Plant Science, 2022)
Plant polysaccharides, a type of important bioactive compound, are involved in multiple plant defense mechanisms, and in particular polysaccharide-alleviated abiotic stress has been well studied. Polygonatum cyrtonema Hua (P. cyrtonema Hua) is a medicinal and edible perennial plant that is used in traditional Chinese medicine and is rich in polysaccharides. Previous studies suggested that sucrose might act as a precursor for polysaccharide biosynthesis. However, the role of sucrose metabolism and transport in mediating polysaccharide biosynthesis remains largely unknown in P. cyrtonema Hua. In this study, we investigated the contents of polysaccharides, sucrose, glucose, and fructose in the rhizome, stem, leaf, and flower tissues of P. cyrtonema Hua, and systemically identified the genes associated with the sucrose metabolism and transport and polysaccharide biosynthesis pathways. Our results showed that polysaccharides were mainly accumulated in rhizomes, leaves, and flowers. Besides, there was a positive correlation between sucrose and polysaccharide content, and a negative correlation between glucose and polysaccharide content in rhizome, stem, leaf, and flower tissues. Then, the transcriptomic analyses of different tissues were performed, and differentially expressed genes related to sucrose metabolism and transport, polysaccharide biosynthesis, and transcription factors were identified. The analyses of the gene expression patterns provided novel regulatory networks for the molecular basis of high accumulation of polysaccharides, especially in the rhizome tissue. Furthermore, our findings explored that polysaccharide accumulation was highly correlated with the expression levels of SUS, INV, SWEET, and PLST, which are mediated by bHLH, bZIP, ERF, ARF, C2H2, and other genes in different tissues of P. cyrtonema Hua. Herein, this study contributes to a comprehensive understanding of the transcriptional regulation of polysaccharide accumulation and provides information regarding valuable genes involved in the tolerance to abiotic stresses in P. cyrtonema Hua.